Use of Potassium Fertilization to Ameliorate the Adverse Effects of Saline-sodic Stress Condition (ECw: SARw Levels) in Rice (Oryza Sativa L.). Issue 16 (8th September 2019) - Munir, Alia; Shehzad, Muhammad Tahir; Qadir, Ayesha Abdul; Murtaza, Ghulam; Khalid, Hafiza Iqra
ABSTRACT: Salt-affected soils expand around the world and become a critical handicap for high crop yield. Saline-sodic soil contributed a major portion in salt-affected soils. Such types of soils have a sizable amount of Na + in nutrient medium and that reduce the K + uptake in plants. A hydroponic experiment was performed to investigate the ameliorative effect of different doses of potassium fertilizer (K1  = 0.3, K2  = 0.6 and K3  = 1.2 mM L −1 ) on rice ( Oryza sativa L.) under different ECw (6 dS m −1 ) and SARw [12 and 24 (mmol L −1 ) 1/2 ] levels. Application of K + at elevated levels under saline-sodic conditions improved the concentration of anti-oxidant enzymes, plant physiological, and biochemical attributes by improving the K + : Na + ratio in plant tissues. Total phenolic content, total soluble protein, and soluble sugar content of rice plant were increased with an increase in potassium dose and saline-sodicity. Maximum K + : Na + ratios, 4.13 and 2.0 were observed in shoot and root, respectively upon application of K + at 1.2 mM L −1 in a solution having ECw : SARw level of 6: 12. This study suggested that application of potassium at elevated levels (1.2 mM L −1 ) has enhanced the rice growth by reducing the harmful effect of Na + salts on plant physiology, biochemical attributes, and anti-oxidant enzymes under specific saline-sodic conditions.